Dead end - Jenkins, Jerry B.; Fabry, Chris, 1961- (Carol Stream, Ill. : Tyndale House, 2006)
Twins Ashley and Bryce face their toughest challenge yet when the terrorist responsible for their father's death seeks revenge against their stepfather, a government agent, and targets schools, beginning with theirs.
4.0
3-6
Keywords: Christian life -- Juvenile fiction; Schools -- Juvenile fiction; Terrorism -- Juvenile fiction; Twins -- Juvenile fiction; Christian life -- Fiction; Mystery and detective stories; Schools -- Fiction; Terrorism -- Fiction; Twins -- Fiction; Christian fiction; Christian life -- Fiction; Mystery fiction; School stories; Terrorism -- Fiction; Twins -- Fiction; Colorado -- Juvenile fiction; Colorado -- Fiction; Colorado -- Fiction; Christian fiction; Mystery fiction